2020
DOI: 10.1186/s13550-020-00709-y
|View full text |Cite
|
Sign up to set email alerts
|

[177Lu]Lu-DOTA-ZOL bone pain palliation in patients with skeletal metastases from various cancers: efficacy and safety results

Abstract: Background [177Lu]Lu-DOTA-ZOL has shown promising results from the dosimetry and preclinical aspects, but data on its role in the clinical efficacy are limited. The objective of this study is to evaluate the efficacy and safety of [177Lu]Lu-DOTA-ZOL as a bone pain palliation agent in patients experiencing pain due to skeletal metastases from various cancers. Methods In total, 40 patients experiencing bone pain due to skeletal metastases were enrolled in this study. The patients were treated with a mean cumul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Patients were asked to record a headache diary about headache intensity (VAS score) before and 2 h after drug intake within 3 months after scanning. According to the criteria, the complete response, partial response, minimal response, and no response were classified as > 75% reduction, 50–75% reduction, 25–50% reduction, and < 25% reduction in VAS scores, respectively ( Yadav et al, 2020 ). The response to NSAIDs was defined as a 50% or greater reduction in pain intensity from pre-treatment level to post-treatment level at least 2 times.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were asked to record a headache diary about headache intensity (VAS score) before and 2 h after drug intake within 3 months after scanning. According to the criteria, the complete response, partial response, minimal response, and no response were classified as > 75% reduction, 50–75% reduction, 25–50% reduction, and < 25% reduction in VAS scores, respectively ( Yadav et al, 2020 ). The response to NSAIDs was defined as a 50% or greater reduction in pain intensity from pre-treatment level to post-treatment level at least 2 times.…”
Section: Methodsmentioning
confidence: 99%
“…Aside from this specific study, the clinical use of [ 68 Ga]Ga-DOTAZOL is also reported for the selection and follow-up of patients considered for TRT with [ 177 Lu]Lu-DOTAZOL [ 182 , 183 , 184 ].…”
Section: Clinical Uses Of Dotazolmentioning
confidence: 99%
“…These studies also revealed higher absorption of the dose by the trabecular bone in patients who received 177 Lu-DOTA-ZOL vs. 177 Lu-EDTMP, but the dose absorbed by critical organs was much lower for the former radiopharmaceutical. Recently, the safety and efficacy of 177 Lu-DOTA-ZOL in 40 patients with metastatic bone disease was evaluated [ 112 ]. Eligible subjects received 0.13 GBq of 177 Lu-DOAT-ZOL at monthly intervals and then were monitored for a 12-week period after therapy.…”
Section: Treatment Of Bone Metastasesmentioning
confidence: 99%